Analysis of the essential oil of monocot grass Kyllinga triceps Rottb. - Upadhyay, Amit; Jain, Vinay; Jain, Suman (Journal of Drug Delivery and Therapeutics, 2019)
Kyllinga triceps rottb. Is a monocot perennial herb found in various parts of india [1]. It is used traditionally by the people for treatment of diabetes, liver problems [2] and as antidote [3]. In the present study chemical constituents of the essential oil, obtained by hydrodistillation of the powdered rhizome of the plant were identified with help of GC-MS. analysis. Ferruginol, β- Caryophyllene, α-Eudesmol, were present in higher concentration, oil sample has a characteristic aromatic odour,which is due to the presence of high amount of linalool, β- Caryophyllene, and α-Eudesmol.Keywords: kyllinga triceps, antidote, rhizome, caryophyllene, α-Eudesmol.